Metacognition and Achievement Emotions in Mathematical Modelling Competency: A Confirmatory Factor Analysis of Their Interplay - Kossahdasabitah, Annisaa; Zulkarnaen, Rafiq (Mosharafa: Jurnal Pendidikan Matematika, 2025)
Penelitian ini menyelidiki hubungan antara metakognitif dan pencapaian emosi dalam pemodelan matematis pada siswa di sebuah SMA Negeri yang berlokasi di Kabupaten Karawang. Penelitian ini melibatkan 200 siswa. Penelitian ini menggunakan desain penelitian korelasional untuk mengetahui hubungan antara metakognitif dan pencapaian emosi dengan menggunakan teknik analisis yaitu analisis faktor konfirmatori. Selain itu, terdapat empat faktor metakognitif termasuk awareness, cognitive strategy, planning, dan self-checking serta dua faktor pencapaian emosi Joy dan Pride yang memiliki hubungan signifikansi sebesar 0,72 sehingga terdapat hubungan yang signifikan antara metakognitif dan emosi. Terdapat faktor planning sebagai faktor dominan metakognitif dan faktor pride sebagai faktor dominan pencapaian emosi yang memiliki hubungan antar satu sama lain. This study aims to examine the relationship between metacognition and achievement emotions in the context of mathematical modeling among students at a public senior high school in Karawang Regency. A total of 200 students participated in the study. The research employed a correlational design, utilizing confirmatory factor analysis (CFA) to analyze the relationship between the two constructs. Metacognition was measured through four factors: awareness, cognitive strategy, planning, and self-checking. Achievement emotions were represented by two factors: joy and pride. The analysis revealed a significant correlation of 0.72 between metacognition and achievement emotions. Furthermore, planning was identified as the most dominant factor within the metacognitive domain, while pride emerged as the dominant factor within the domain of achievement emotions. These two dominant factors were also found to have a significant relationship with one another.